Construction and Validation of a Scale for Assessing Best Intercultural Practices in Social Work - Vázquez-Aguado, Octavio; Fernández-Borrego, Manuela A.; Fernández-Santiago, Miriam; Vaz-García, Patricia (Cuadernos de Trabajo Social, 2012)
This article reports on the construction and validation process of an instrument that enables the placement of intercultural projects on a scale of Best Practices. The validated scales includes 32 variables divided into four categories: theoretical (subdivided further into three categories: contextual, concept of diversity and elements of diversity); ethicalideological, sociopolitical and intercultural empathy. Questions related to project identification are also included. The scale was piloted in social intervention projects in different sectors sharing the intercultural vision (employment, education, health, etc.) and was developed in Andalusia (Spain). The data obtained show evidence of construct validity and high reliability of the instrument as designed.